Radiological images of interstitial pneumonia in mixed connective tissue disease compared with scleroderma and polymyositis/dermatomyositis. Issue 107 (October 2018) - Yamanaka, Yumie; Baba, Tomohisa; Hagiwara, Eri; Yanagawa, Noriyo; Takemura, Tamiko; Nagaoka, Shohei; Sakai, Fumikazu; Kuwano, Kazuyoshi; Ogura, Takashi
Abstract: Objective: Little has been reported on the radiological and pathological findings of interstitial pneumonia in mixed connective tissue disease (MCTD). There may be possible difference in treatment response and prognosis between the imaging patterns of systemic sclerosis (SSc)-like and polymyositis/dermatomyositis (PM/DM)-like. The purpose of this study was to examine whether the radiological images of interstitial pneumonia in MCTD presented SSc-like or PM/DM-like pattern, and to assess whether the imaging patterns corresponded to clinical and pathological features. Materials and methods: This retrospective study included 29 patients with interstitial pneumonia who underwent surgical lung biopsy; 10 with SSc, 10 with PM/DM, and 9 with MCTD. High resolution computed tomography (HRCT) images were classified as SSc, PM/DM, or the other pattern by two radiologists independently without clinical information. The pathology of the lung specimens from MCTD patients were evaluated and compared with the imaging pattern. Results: The concordance rate between clinical diagnosis and radiological pattern was 100% in SSc patients, and 80% in PM/DM patients. Among patients with MCTD, imaging patterns were classified as SSc pattern in 4 (MCTD-SSc), PM/DM pattern in 4 (MCTD-PM/DM) and other in one. The imaging patterns did not always correlate with the clinical findings in MCTD patients. Pathologically, plasma cell infiltration and organizing pneumonia were relatively more frequent in MCTD-PM/DM, and smooth muscle hyperplasia was relatively more frequent in MCTD-SSc. Conclusion: HRCT images in MCTD patients can be classified as SSc pattern or PM/DM pattern. MCTD-SSc and MCTD-PM/DM were corresponded to similar pathological findings of SSc and PM/DM.